2014
DOI: 10.1007/s10964-014-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Relationships Between Sleep Problems and Substance Use, Internalizing and Externalizing Problems

Abstract: While research has shown that sleep problems and substance use are reciprocally associated in adults, much less is known about this association in early adolescence. The main aim of the current longitudinal study was to explore bidirectional relationships between sleep problems, substance use, internalizing and externalizing problems in young adolescents. A prospective design was used incorporating two waves (approximately 1 year interval). A total of 555 young adolescents (290 females, M age = 13.96) particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
87
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 58 publications
19
87
1
1
Order By: Relevance
“…Moreover, obtaining just 1 h less of weekday sleep was associated with increased odds of hopelessness, suicidal ideation, suicide attempts, and substance use. These findings are consistent with those of Pieters et al (2015) who found that sleep problems prospectively predicted increased substance use, internalizing symptoms, and externalizing problems 1 year later in a sample of 555 adolescents (ages 11-16 years), even after controlling for baseline levels of adjustment, age, sex, and pubertal development. Of note, no evidence was found for reverse associations of substance use, internalizing symptoms, or externalizing problems predicting later sleep problems, with the exception of alcohol use predicting increased sleep difficulties 1 year later.…”
Section: Overview Of Special Issue Contributionssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, obtaining just 1 h less of weekday sleep was associated with increased odds of hopelessness, suicidal ideation, suicide attempts, and substance use. These findings are consistent with those of Pieters et al (2015) who found that sleep problems prospectively predicted increased substance use, internalizing symptoms, and externalizing problems 1 year later in a sample of 555 adolescents (ages 11-16 years), even after controlling for baseline levels of adjustment, age, sex, and pubertal development. Of note, no evidence was found for reverse associations of substance use, internalizing symptoms, or externalizing problems predicting later sleep problems, with the exception of alcohol use predicting increased sleep difficulties 1 year later.…”
Section: Overview Of Special Issue Contributionssupporting
confidence: 89%
“…In contrast, initial levels of depressive symptoms in the spring of the senior year of high school predicted increased subjective sleep problems and actigraphy-measured sleep onset latency and sleep start variability in the fall of the first year of college. In considering these results alongside the findings of Pieters et al (2015), it is possible that a developmental progression occurs whereby sleep problems confer risk for depressive symptoms in early-to-mid adolescence whereas the presence of depressive symptoms in late adolescence impacts subsequent sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 92%
“…Recent research has begun to explore potential mechanisms through which sleep problems lead to these negative behavioral outcomes. Specifically, evidence suggests that decreased sleep quantity and quality negatively impacts cognitive functioning within the prefrontal cortex, which is associated with decreased inhibition and increased impulsivity, ultimately leading to the greater likelihood of engaging in risk-taking behaviors such as drug use and delinquent acts (Peach and Gaultney 2013; Pieters et al 2015). Continued research investigating this link will help to uncover how sleep problems lead to externalizing outcomes in at-risk youth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a longitudinal study from the National Longitudinal Study of Adolescent Health found that sleep difficulties at earlier waves significantly predicted the use of substances as well as substance-related problems at later waves (Wong, Robertson, & Dyson, 2015). Another longitudinal study found bidirectional relationships between sleep problems and substance use in young adolescents (Pieters et al, 2015). Given the adverse consequences of insomnia, the present study was designed to examine the predictors of insomnia to increase understanding of its genesis.…”
Section: Introductionmentioning
confidence: 99%